(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today, more than 100,000 children and adolescents worldwide have DM. The peak of morbidity falls on the early pubertal period. Moreover, the pathogenetic basis of specific complications is quite high, up to 90% (3, 8). Diabetic neuropathy (DN) is the most frequent and at the same time poorly studied complication of DM in childhood. The low visibility of DN in childhood is due to the difficulties in diagnosis, due to the non-severe, including subclinical (asymptomatic) variants of the course; the diagnostic process itself is limited, as the main diagnostic methods for detecting DN have been developed for the adult population.